1993
DOI: 10.1099/0022-1317-74-5-811
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Antibody Response to the Latent Infection Terminal Proteins of Epstein-Barr Virus in Patients with Nasopharyngeal Carcinoma

Abstract: Human sera were tested for antibodies against the Epstein-Barr virus (EBV) latent infection terminal proteins (TPs). Anti-TP IgG and IgA antibodies were detected by an indirect immunofluorescence assay of insect cells expressing a recombinant TP1. Out of 301 human sera of patients with EBV-related and EBVunrelated disorders, only sera from patients with nasopharyngeal carcinoma (NPC) (32/83; 38 %) showed anti-TP antibodies. Studies on serial sera from German and Hong Kong NPC patients revealed a decline of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
5
10
1
Order By: Relevance
“…This finding supports earlier work in which antibody responses to LMP2A and LMP2B were detected in sera from NPC patients but not in sera from patients with other EBV-related disorders (11). The immunoreceptor tyrosine-based activation motif (ITAM) of LMP2A, like that present in the B cell receptor (BCR), is tyrosine-phosphorylated and associates with the src family of protein tyrosine kinases and the syk protein tyrosine kinase (12).…”
Section: Epstein-barr Virus (Ebv)-associated Malignancies Display Dissupporting
confidence: 79%
“…This finding supports earlier work in which antibody responses to LMP2A and LMP2B were detected in sera from NPC patients but not in sera from patients with other EBV-related disorders (11). The immunoreceptor tyrosine-based activation motif (ITAM) of LMP2A, like that present in the B cell receptor (BCR), is tyrosine-phosphorylated and associates with the src family of protein tyrosine kinases and the syk protein tyrosine kinase (12).…”
Section: Epstein-barr Virus (Ebv)-associated Malignancies Display Dissupporting
confidence: 79%
“…However, Frech et al (17) reported no fluctuation, nor did we recognize any fluctuation. A possible explanation for these contradictory results may be that EBV is now suspected to be reactivated in NPC because several lytic-cycle genes are expressed in NPC (16,21,22), and the IgA reaction to this reactivation of EBV in NPC might vary depending on the individual case, the patient's race or the area where the patient lives.…”
Section: Discussioncontrasting
confidence: 49%
“…As for HPC and MPC, we detected EBV expression by means of mRNA in situ hybridization using BamHIW probes and by immunofluorescence staining (16), and this may explain the presence of IgA/VCA antibody in HPC. Recently, moreover, Frech et al (17) reported that anti-TP antibody is specific to NPC, and Liu et al showed that antibody against BHRF1 was specific for the diagnosis of NPC (18).…”
Section: Discussionmentioning
confidence: 99%
“…The present data indicating that the LMPs are only weakly immunogenic accord with the finding that the LMPs only induce detectable humoral responses in rare circumstances; thus anti-LMP1 antibodies have been detected in a subset of patients with HD or NPC but not in most healthy carriers, 23,31,32 while anti-LMP2 antibodies have only been described in NPC patients. 23,33,34 Furthermore, our recent studies have shown that LMP1 and LMP2 are also a poor source of epitopes for the CD4 ϩ T cell response. 35 Why these molecules should be relatively poorly immunogenic is not understood.…”
Section: Discussionmentioning
confidence: 99%